Karakteristik Enkapsulat Ekstrak Pewarna Bunga Kenop (Gomphrena globosa L.) pada Perlakuan Perbandingan Gum Arab dan Karagenan - Naz, Amenra Ramzi; Wrasiati, Luh Putu; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): Maret, 2022)
Globe amaranth flowers can be used as food coloring because they contain betacyanin. Betacyanin compounds obtained by extraction and stored in the form of encapsulated powder. The aims of this study were (i) to determine the effect of the comparison of gum arabic and carrageenan as an encapsulation material on the characteristics of the encapsulated extract of globe amaranth flower dye extract, and (ii) to know the best comparative treatment of gum arabic and carrageenan to produce globe amaranth flower dye encapsulates. The experiment in this study used a randomized block design with a comparison of gum arabic and carrageenan consisting of 7 levels, namely (1:0), (0:1), (1:1), (1:1,5), (1: 2), (1:2,5) and (1:3). The results showed that the comparison of gum arabic and carrageenan had an effect on yield, water content, solubility, total betacyanin content, surface betacyanin content, encapsulation efficiency, brightness level (L), redness level (a*), yellowness level (b*), and antioxidant capacity. The best treatment in producing the encapsulated extract of the globe amaranth flower dye was the ratio of gum arabic and carrageenan (1:2) with the characteristics of yield 93,51%, water content 10,35%, solubility 41,75%, total betacyanin content of 233,75 mg/100g, surface betacyanin content 47,361 mg/100g, encapsulation efficiency 79,72%, brightness level (L*) 27,66, level of redness (a*) 17,37, level of yellowness (b*) 14,43, and antioxidant capacity 80,13 mg GAEAC/g. Keywords: betacyanin, carageenan, comparison, encapsulation, gum arabic.